Iconografia do trabalho: a desconstrução do neoliberalismo no Brasil a partir da obra de Sebastião Salgado - Câmara, Rayanne Aversari (2019)
Among global efforts regarding international norms and principles of labor, the social value of work and decent work, neoliberal measures have been implemented in Brazil, such as Law 13467 of 2017 (Labor Reform), which, despite promising to modernize and adapt the legislation to the new labor relations, actually makes it more precarious, disarms the Labor Law, and infringes, among many others, the principle of protection. At this juncture, the interest in maximizing profit through cheaper labor, although always present, now finds legal support, a fact that means a retreat from work at the beginning of the process of industrialization of the country and, consequently, increases the exposure of the worker to degrading conditions. On the other hand, the perception of this exposition cannot be summed up to the historically formalistic techniques of Law, which have proved to be insufficient, given the evolution of social complexity. In this regard, through interdisciplinary studies between law and art, the work: “Workers: An Archaeology of the Industrial Age”, by Sebastião Salgado, seeks a better understanding of the social regression imposed on Brazilian workers through the entry into force of the Labor Reform. Accordingly, it is intended to answer if, in the light of the iconography of work, it is possible to apply the deconstruction of neoliberal ideology in Brazil. The hypothesis raised is that the iconography of work, especially the archaeological photography of Sebastião Salgado, is an effective interdisciplinary way of denouncing that the real purpose of the neoliberal ideology implemented in Brazilian socioeconomic context is to maximize profit by exploiting the worker and reducing it to the labor force and, therefore, is a convenient way of influencing social behavior, imposing a new look of resistance and especially of transformation in the sense that labor must be a means of emancipation for the citizen. In this way, based on work “Workers: An Archaeology of the Industrial Age”, it is intended to analyze how the iconography of work can be an instrument of deconstruction of the neoliberal ideology in Brazil. From the theoretical-methodological perspective of historical-dialectical materialism, it is evaluated the cyclical socioeconomic components of capitalism, which have imposed a series of social setbacks to the workers' struggles. It is concluded that as a result of neoliberal measures, Brazilian workers were reduced to the labor force and had their rights restricted, their access to justice limited, the labor became more precarious and social value of work was usurped, being truly massacred, currently reflecting the patterns of exploitation portrayed in the work “Workers: An Archaeology of the Industrial Age”.